2012
DOI: 10.5114/ninp.2012.28257
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of accelerometric registration with assessment of tremor parameters and their symmetry in differential diagnosis of parkinsonian, essential and cerebellar tremor

Abstract: Standard deviation of centre frequency and harmonic index are the most valuable variables in differentiation of tremor. The assessment of symmetry of tremor parameters is useful in discrimination of various types of pathological tremor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Multiple studies have explored using harmonics of tremor motion to identify different types of pathological tremors. Majchrzak et al demonstrated that, compared to healthy controls, the harmonic index of tremor motions (the distance of the spectrum to the single narrow peak, which was normalized to the highest peak) was significantly higher in patients with Parkinsonian tremor, essential tremor, and cerebellar tremor ( 24 ). Jang et al reported that the harmonic ratio (the value of the total harmonic peak power divided by the number of harmonic peaks) was remarkably lower in PD patients than in drug-induced Parkinsonism patients ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have explored using harmonics of tremor motion to identify different types of pathological tremors. Majchrzak et al demonstrated that, compared to healthy controls, the harmonic index of tremor motions (the distance of the spectrum to the single narrow peak, which was normalized to the highest peak) was significantly higher in patients with Parkinsonian tremor, essential tremor, and cerebellar tremor ( 24 ). Jang et al reported that the harmonic ratio (the value of the total harmonic peak power divided by the number of harmonic peaks) was remarkably lower in PD patients than in drug-induced Parkinsonism patients ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature cites only a few references concerning the correlation of tremor with hand laterality. For example, Machowska-Majchrzak discovered that the essential tremor was more intense in the N extremity in 62% of patients [44,45]. In contrast, no correlation of arm swing in walking was identified with laterality, possibly due to an important central component in this involuntary movement [46].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between tremor intensity or frequency in ET and PD is controversial. An inverse correlation between tremor intensity and centre frequency was found in ET patients while patients with PD showed only significant correlation between centre frequency and the hand with more severe tremor, not in the other hand (Machowska-Majchrzak et al, 2012). Other studies reported a significant inverse correlation between tremor intensity and centre frequency in both hands in patients with PD (Farkas et al, 2006).…”
Section: Current Approaches For Diagnosis Of Et and Pdmentioning
confidence: 98%